2007
DOI: 10.1080/15563650601181562
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative measurement of cyanide released from Prussian Blue

Abstract: PB had the highest cyanide release at pH 1 (135 ug/g) and lowest release at pH 5.0-7.0 from the highest daily dose of PB (17.5 g) (21 ug/g). Considering the minimal lethal dose of cyanide is approximately 50 mg, the maximal cyanide released (1.6 mg) does not present a safety concern.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
50
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(55 citation statements)
references
References 24 publications
4
50
0
1
Order By: Relevance
“…This observation is consistent with the fact that the single crystals of PB were first obtained from a 12 M HCl solution. Our results of acid stability studies are also in line with the findings made by the US Food and Drug Administration (FDA) on the release of cyanide from PB prior to the approval of bulk PB as the oral antidote for the internal contamination of radioisotopes of cesium and thallium [35]. The quantitative measurements in that study showed that the highest cyanide release at pH 1 is 135 lg/g which corresponds to a total release of 1.6 mg cyanide for the highest daily dose of 17.5 g for a 70 kg adult.…”
supporting
confidence: 92%
“…This observation is consistent with the fact that the single crystals of PB were first obtained from a 12 M HCl solution. Our results of acid stability studies are also in line with the findings made by the US Food and Drug Administration (FDA) on the release of cyanide from PB prior to the approval of bulk PB as the oral antidote for the internal contamination of radioisotopes of cesium and thallium [35]. The quantitative measurements in that study showed that the highest cyanide release at pH 1 is 135 lg/g which corresponds to a total release of 1.6 mg cyanide for the highest daily dose of 17.5 g for a 70 kg adult.…”
supporting
confidence: 92%
“…The physical adsorption and ion trapping process may be affected as well, but possibly to a lesser extent. We have found cyanide release from PB was also pH dependent: the lower pH, the higher cyanide release (Yang et al, 2007b). Similar results were reported by other authors (Verzijl et al, 1993).…”
Section: Discussionsupporting
confidence: 81%
“…Prussian Blue analogues are known to be more stable at acidic pH than in neutral and basic pH, as ligand exchange between the CN À ligands and OH À ions results in the dissolution and destruction of the Prussian Blue structure 29 . This trace solubility is the dominant loss mechanism during their operation in both battery electrodes and electrochromic devices, thereby acidic pH has been found to extend the lifetimes of these devices 30 .…”
Section: Resultsmentioning
confidence: 99%